The Lake Shore Limited [large type] - Miller, Sue, 1943- (Random House Large Print, 2010)
The Lake Shore Limited is a play about the terrorist bombing of that train and about a man waiting to hear the fate of his estranged wife who is traveling on it. How Billy comes to write the play out of her own painful conflicts and ambivalence, how it is then created anew by the actors and the director, how the performance itself touches and changes the other characters' lives.